Leptin/Melanocortin Pathway in Cholelithiasis Patients: A Diagnostic Perspective - Agbektas, Tugba; Guclu, Gulsen; Tas, Ayca; Ozmen, Esma; Topcu, Omer; Aydin, Suleyman; Silig, Yavuz (Bentham Science Publ Ltd, 2025)
Background: Cholelithiasis is the most prevalent inflammatory condition of the gallbladder. The regulation of biological processes, including energy homeostasis, and control of body weight are key mechanisms that the leptin and melanocortin pathways play a role in Cholelithiasis is the most prevalent inflammatory condition of the gallbladder. There are various risk factors for the development of gallstone disease, especially weight gain, and obesity is just one of them. This risk factor can be minimized by maintaining appetite and energy balance. Here, leptin and melanocortin pathways are the key mechanisms in maintaining appetite and energy homeostasis. Objectives: The aim of this study was to investigate the relationship between the levels of LEP, LEPR, TrkB, BDNF, POMC, and MC4R proteins in patients with Cholelithiasis. This study aims to determine the relationship between LEP, LEPR, TrkB, BDNF, POMC, and MC4R protein levels, which play a role in maintaining appetite and energy homeostasis, and cholelithiasis. Methods This study examined 44 patients diagnosed with Cholelithiasis and 44 healthy control subjects who had not previously been diagnosed with any form of Cholelithiasis. The levels of leptin (LEP), Leptin Binds To Leptin Receptors (LEPR), Tropomyosin Receptor Kinase B (TrkB), Brain-Derived Neurotrophic Factor (BDNF), Pro-OpioMelanoCortin (POMC), and Melanocortin-4 Receptors (MC4R) molecules were analyzed using the Enzyme-Linked Immunosorbent Assay (ELISA) method. The results were analyzed using the SPSS Software (Version 22.0) program and GraphPad Prism 8.0.1 software. Results: The study found a statistically significant decrease (p < 0.05) in MC4R, TrkB, BDNF, and POMC protein levels in Cholelithiasis patients compared to the control group. There was no statistically significant difference in LEP and LEPR concentration values between the two groups (p = 0.247, p = 0.674). Conclusion: The proteins MC4R, TrkB, BDNF, and POMC, which are involved in the leptin and melanocortin pathways may play a significant role in Cholelithiasis disease. However, more detailed research on the relevant proteins is needed. Nevertheless, this research will guide new studies.
Keywords: Cholelithiasis; leptin-melanocortin pathway; LEP; LEPR; TrkB; BDNF; POMC; MC4R